Increased Prevalence of Abnormal Glucose Tolerance among Obese Siblings of Children with Type 2 Diabetes - Magge, Sheela N. (2008)
OBJECTIVE: To test the hypothesis that overweight siblings of children with type 2 diabetes mellitus (T2DM) have a higher prevalence of abnormal glucose tolerance (AGT) compared with other overweight children. STUDY DESIGN: This was a cross-sectional study of overweight (body mass index [BMI] ≥ 95(th) percentile) subjects, age 8 to 17 years, with at least 1 sibling age ≥ 12 years. The primary outcome was AGT, as assessed by the oral glucose tolerance test (2-hour glucose ≥ 140 mg/dL). The secondary outcome was insulin resistance by homeostasis model assessment (HOMA). RESULTS: The sibling (n = 20) and control (n = 42) groups were similar in terms of age, sex, racial distribution (largely African American), pubertal status, and BMI. The prevalence of AGT in the sibling group was 40.0% (n = 8), compared with 14.3% (n = 6) in controls (P = .048, Fisher exact test; unadjusted odds ratio = 4.0; 95% confidence interval = 1.2 to 13.5). Univariate analysis did not identify confounders for either outcome. There were no significant differences in HOMA or hemoglobin A1c between the 2 groups. CONCLUSIONS: Overweight siblings of children with T2DM had 4 times greater odds of having AGT compared with other overweight children. This group may represent a particularly high-risk population to target for screening and pediatric T2DM prevention.